Motor Vehicle Tax Contribution to Regional Original Income in Banten Province - Hermawan, Iwan; Myrna, Rita; Nurasa, Heru; Karlina, Nina (KnE Social Sciences, 2022)
This study aimed to investigate the contribution of motor vehicle tax to regional original income (PAD) in Banten Province. Income is an important element in the implementation of development activities. In each region, development activities have been increasing from year to year and this is associated with large costs, which therefore encourages an increase in PAD. One of the sources of PAD is motor vehicle tax, which is one of the local tax forms regulated by Law no. 28 of 2009 concerning regional taxes and levies chapter II, part one, article 2. This law designates that regional taxes are the authority of the province and consist of 1. motorized vehicle transfer fees, 2. motorized vehicle taxes, 3. surface water tax, 4. motor vehicle fuel tax, and 5. cigarette tax. Out of these five types of regional taxes, the motor vehicle tax is the most dominant contributor to regional income each year in Banten Province. Keywords: motor vehicle tax, regional original income, regional tax